2009
DOI: 10.1213/ane.0b013e3181a89641
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Propofol Infusion on Hepatic and Pancreatic Function and Acid-Base Status in Children Undergoing Craniotomy and Receiving Phenytoin

Abstract: Despite the slightly increased pancreatic and hepatic enzyme levels during the postoperative period, anesthesia maintenance with propofol in children undergoing craniotomy had no significant clinical effect on the acid-base status or pancreas or liver enzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 36 publications
3
9
0
2
Order By: Relevance
“…It is suggested that propofol might be suitable for anesthesia management in pancreatic cancer patients. Related clinical treatments have also confirmed that propofol anesthesia helps reduce postoperative complications and improve long-term survival of patients with pancreatic cancer [50][51][52].…”
Section: Discussionmentioning
confidence: 88%
“…It is suggested that propofol might be suitable for anesthesia management in pancreatic cancer patients. Related clinical treatments have also confirmed that propofol anesthesia helps reduce postoperative complications and improve long-term survival of patients with pancreatic cancer [50][51][52].…”
Section: Discussionmentioning
confidence: 88%
“…There have also been reports of increases in transaminases (GOT, GPT), gamma-glutamyl transpeptidase (GGT), amylase, triglycerides and lipase in the immediate postoperative period, 31 as well as an increase in nosocomial infections, respiratory depression, epileptiform movements, headache, greenish colored urine, thrombosis, phlebitis, pancreatitis and postoperative fever. Among the effects reported in under 1% of the cases, mention should be made of amblyopia, restlessness, sialorrhea, hypomagnesemia, blistering or necrosis secondary to accidental extravasation, laryngeal spasms, cardiac arrhythmias and lung edema.…”
Section: Discussionmentioning
confidence: 99%
“…Propofol ve pankreatit arasındaki ilişki henüz kanıtlanamamıştır ve konu ile ilgili az sayıda çalışma ve vaka raporu mevcuttur. Propofole bağlı pankreatit patogenezi için; propofolün formülasyonuna bağlı olarak hipertrigliseridemiye yol açabileceği ve trigliseridlerin pankreasta hidrolizine bağlı olarak ortaya çıkan serbest yağ asitlerinin asiner hücre ve kapillerlerde hasara neden olabileceği ayrıca pankreatik kapillerlerin şilomikronlarla tıkanarak iskemiye neden olabileceği görüşü ortaya atılmıştır (47). Asidotik durum ve yüksek serbest yağ asidi seviyelerinin kombinasyonu tripsinojeni aktive eder ve akut pankreatiti başlatabilir (47).…”
Section: Bulgularunclassified
“…Propofole bağlı pankreatit patogenezi için; propofolün formülasyonuna bağlı olarak hipertrigliseridemiye yol açabileceği ve trigliseridlerin pankreasta hidrolizine bağlı olarak ortaya çıkan serbest yağ asitlerinin asiner hücre ve kapillerlerde hasara neden olabileceği ayrıca pankreatik kapillerlerin şilomikronlarla tıkanarak iskemiye neden olabileceği görüşü ortaya atılmıştır (47). Asidotik durum ve yüksek serbest yağ asidi seviyelerinin kombinasyonu tripsinojeni aktive eder ve akut pankreatiti başlatabilir (47). Genel olarak hiperlipideminin pankreatite yol açabilmesi için trigliserid seviyelerinin uzun süre 1000-2000 mg/dL'nin üzerinde seyretmesi gerektiğine inanılmakta; propofolün yol açtığı geçici ve ılımlı trigliserid yük-selmesinin pankreatite yol açıp açmayacağı konusu ise hala tartışılmaktadır (48,49).…”
Section: Bulgularunclassified